Evaluating a Constructivist Model for Learning Clinical Skills in Pre-Clinical Years of a Dental Curriculum - Osama Khattak, Ambreen Usmani, Junaid Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to investigate whether or not using a constructivist model for teaching clinical skills had an impact on students’ performance in a pre-clinical operative dentistry course. Study Design: Randomized Control Trial Place and Duration: College of Dentistry, Jouf University, Saudi Arabia, two months (March and April 2022). Methods: A total of 50 second year BDS students participated in this trial. The students were divided randomly into two groups. Group I received traditional method and group II received constructivist method. The students’ capability of performing rubber dam application skill on the typodont tooth was evaluated through the use of laboratory activities. After the conclusion of the research, the participants were given a questionnaire to complete out and provide feedback on. Examinations that were objective and systematic were performed on both groups clinically (OSCEs). Results: There was a statistically significant difference in learning modes (p 0.001). The students learning method has nothing to do with their age or gender. Group II (constructivist) demonstrated considerably higher development in scores across lab tasks (p<0.05). While students of all backgrounds valued supplemental learning resources, those who got aligned materials reported feeling more grateful for them. Conclusion: The constructivist approach can be used as a complementary teaching strategy in pre-clinical operative dentistry courses to improve students’ learning outcomes and prepare them for success in the dental profession. Keywords: preclinical education, predoctoral education, learning styles, operative dentistry, and education.